Decision Framework to Balance Environmental, Technical, Logistical, and Economic Criteria When Designing Structures With Reused Components - Küpfer, Célia; Bertola, Numa; Brütting, Jan; Fivet, Corentin (Frontiers in Sustainability, 2021)
The reuse of structural components in new buildings has great potential to reduce the environmental impacts of the construction sector but remains uncommon practice. An obstacle to its wider implementation is the lack of robust assessment methods and decision-making tools that consider the full spectrum of benefits and drawbacks. This paper proposes a multi-criteria decision framework that builds on a simulated set of design alternatives with varying ratios of reused and new structural components. A set of performance criteria is presented, addressing procurement risks, construction technique complexity, environmental impacts, and project costs. As the independent criterion evaluations often deliver conflicting results, a multi-criteria decision analysis helps identify the most appropriate solution. The design of a steel Pratt truss is used as a case study to demonstrate the applicability of the framework. Different alternatives with reuse rates above 65 % are recommended for each preference scenario, reducing between 35 and 45 % of adverse environmental impacts in comparison to an equivalent design made of new elements only. The study underpins the principle that there is no trivial and unique best option when designing with reused components. Multi-criteria decision analyses applied to structures with varying reuse rates constitute a promising tool to support decision-makers.